Hofstede’s Cultural Dimensions – A Study of Filipino Canadians - Estrella, Dave (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Understanding Hofstede’s Cultural Dimensions is the tool that this researcher used to examine the cultural differences between Philip-pines and Canada, as well as new emerging culture of the Filipino Ca-nadians as a sub-group of cultures. This research study examines the different cultural dimensions - Power Distance, Uncertainty Avoid-ance, Individualism / Collectivism, Masculinity / Femininity, and Short Term / Long Term Orientation to understand the factors affect-ing the underrepresentation of Filipino Canadian Engineers in the Architecture, Engineering and Construction (AEC) industry in Canada. The respondents of this research study are internationally trained Filipino Canadian Engineers who are also members of the Associa-tion of Filipino Canadian Engineers (AFCE). The researcher used a combination of self-made Survey Questionnaires published on Google Forms and face-to-face interviews. The questionnaires were sent via email and/or social media platforms such as Messenger and LinkedIn. The data collected were tallied, analyzed, interpreted and summa-rized using statistical treatments such as Mean, Pearson r correlation, Standard Deviation and Frequency. The study revealed that Filipinos have assimilated well into the Canadian Society in terms of the Hof-stede’s Cultural Dimensions with the exemption of Collectivism. In terms of Power Distance, Filipino Canadians revealed a low score while in the Motivation towards Achievement and Success, Filipino Canadians prefer a more work-life balance, both comparable to Cana-dians. The study also revealed that many Filipino Canadian Engineers feel that they are underrepresented in the Engineering and Construc-tion industry in their new home, Canada. Filipinos should start con-versations on Diversity and Inclusion to mitigate this problem. These findings will help community leaders to develop courses and pro-grams that will help pave the way for Filipinos to effectively assimi-late to a diverse and inclusive Canadian society.